(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Isatin and substituted Isatin were reacted with 4-amino-N-carbamimidoyl benzene sulfonamide to form a series of Schiff’s bases. The Mannich bases of these compounds were synthesized by reacting them with formaldehyde and secondary amine (piperidine). All the compounds were characterized by means of their IR, 1H NMR spectroscopic data and elemental analysis. The antimicrobial activity of the synthesized compounds was evaluated by tube dilution method. The synthesized compounds showed better antibacterial activity than the reference drugs.